Classroom Discourse of English Language Classes in the Terai of Sudurpaschim Province - Jora, ManaBahadur (Journal of NELTA Gandaki, 2021)
This article focuses on the classroom discourse of English language class in the Terai region of Sudurpaschim Province. It analyses the classroom discourse of secondary level English language classes. Classroom discourse in the English language class in the Terai region of Sudurpaschim Province has not been studied yet. Similarly, it aims to explore how classroom discourse is practiced in the English language classes and find out ways using English language from the linguistic perspective. Classroom discourse reciprocates the cultural development. Simultaneously, this article tries to show that classroom discourse is means of motivation and the study contends to show that classroom discourse is a means of interaction. Students and teachers can reflect their conceptualization in the class. Additionally, classroom discourse maintains cognitive aspect of teachers and learners. In the English language classroom, classroom discourse works as source of interaction and motivation. Furthermore, it provides opportunities to students. Thus, classroom interaction is the use of language in the class that we term as classroom discourse.